URGENSI PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM BERWAWASAN KEBANGSAAN - Anwar, Syaiful; Fiah, Rifda El (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract Developing the character of students will love the homeland, uphold peace, and be able to work productively, respect differences (pluralism), maintain unity and unity as a very important basic framework which is the role of Islamic education, so that it must always be nurtured and sown on each individual learner through education and teaching with nationalism insight. In accordance with its basic role which is always oriented to the future and the benefit of the people, the writer seeks to discuss the development of a national-minded Islamic education curriculum which is currently very much needed in the framework of giving birth to the next generation with a better quality of understanding, service and nationalism than current generation.The method used in this research is descriptive qualitative method with the type of research that is library research. The results of data analysis that the development of nationally-minded Islamic education has quantitative meanings and qualitative meanings. Quantitatively the development of Islamic-minded Islamic education can be done by increasing the reading references, expanding socialization, making forums, and developing a culture that accommodates national values in Islamic education, quantitatively developing components that need to be developed is strengthening the theoretical foundation and the translation, developing the curriculum, improving the quality of teaching staff, and education, financing and reviving local traditions / culture that do not conflict with the spirit and values of existing Islam. Keywords: Urgency, Islamic Education Curriculum, and Nationality Insight. Abstrak Menumbuh kembangkan karakter peserta didik akan cinta tanah air, menjunjung perdamaian, dan dapat bekerja sama secara produktif, menghargai perbedaan (pluralisme), menjaga persatuan dan kesatuan sebagai kerangka dasar yang sangat penting yang merupakan peran dari pendidikan Islam, sehingga harus selalu dipupuk dan disemai pada setiap pribadi peserta didik melalui pendidikan dan pengajaran yang berwawasan kebangsaan. Sesuai dengan peran dasarnya yang selalu berorentasi ke masa depan dan kemaslahatan umat, maka penulis berupaya membahas tentang pengembangan kurikulum pendidikan Islam berwawasan kebangsaan yang saat ini sangat diperlukan dalam kerangka untuk melahirkan generasi penerus bangsa dengan kualitas pemahaman, jasa dan semangat kebangsaan yang lebih baik dibandingkan dengan generasi sekarang. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan jenis penelitian yaitu penelitian kepustakaan (library research). Adapun Hasil analisis data bahwa Pengembangan pendidikan Islam berwawasan kebangsaan memiliki makna kuantitatif dan makna kualitatif. Secara kuantitafif pengembangan pendidikan Islam berwawasan kebangasaan dapat dilakukan dengan memperbanyak referensi bacaan, memperluas sosialisasi, membuat forum-forum, serta membangan kultur yang mengakomodasi nilai-nilai kebangsaan dalam pendidikan Islam, pengembangan secara kuantitatif yaitu komponen-komponen yang perlu dikembangknan adalah penguatan landasan teori dan penjabarannya, mengembangkan kurikulum, meningkatkan kualitas SDMtenaga pendidik, dan kependidikan, pembiayaan serta menghidupkan tradisi/budaya lokal yang tidak bertentangan spirit dan nilai-nilai islam yang ada. Kata Kunci: Urgensi, Kurikulum Pendidikan Islam, dan Wawasan Kebangsaan.